An ill wind? Terrorist attacks and CEO compensation - Dai, Yunhao; Rau, P. Raghavendra; Stouraitis, Aris; Tan, Weiqiang (Journal of Financial Economics, 2020)
Using multiple measures of attack proximity, we show that CEOs employed at firms located near terrorist attacks earn an average pay increase of 12% after the attack relative to CEOs at firms located far from attacks. CEOs at terrorist attack-proximate firms prefer cash-based compensation increases (e.g., salary and bonus) over equity-based compensation (e.g., options and stocks granted). The effect is causal and it is larger when the bargaining power of the CEO is high. Other executives and workers do not receive a terrorist attack premium.